Natural history in Malan syndrome: survey of 28 adults and literature review - T. N. Huynh; C. G. Delagrammatikas; L. Chiriatti; A. Panfili; K. Ventarola; L. A. Menke; M. Tartaglia; S. A. Huisman; M. Priolo (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Malan syndrome (MALNS), previously referred to as “Sotos syndrome 2” due to its resemblance to Sotos syndrome (SS), is an ultra-rare neurodevelopmental disorder characterized by overgrowth, typical craniofacial features, intellectual disability (ID), and a range of psychobehavioral, musculoskeletal, vision and neurological signs. As MALNS and SS partly overlap, it is essential to more accurately profile their clinical presentations and highlight their differences in order to improve syndrome specific management. An increasing number of individuals with MALNS reach adult-age though the natural history of the disorder is poorly characterized due to the small number of adult individuals described so far. As a consequence, current guidelines are limited to the pediatric population. Further delineation of MALNS is essential to optimize care in adulthood. Results A mixed approach based on cross-sectional data collection with a survey disseminated to caregivers of adults with molecularly confirmed MALNS and literature review was conducted. Twenty-eight caregivers completed the survey. Clinical presentation in adulthood is multisystemic and defined by psychobehavioral comorbidities (96%), musculoskeletal involvement (96%), vision impairment (96%) and neurological complications (86%). The most common signs were anxiety (79%), hypotonia (75%), movement difficulty (75%), scoliosis (64%), problems with coordination (61%), strabismus (57%), constipation (54%), breastbone abnormalities (54%) and advanced bone age during childhood (54%). Impaired vision was complicated by vision decline (36%) and optic atrophy (32%). We report some previously unidentified features, including high pain threshold (46%), incontinence (25%), tremors (21%), muscle hypoplasia (18%) and tics (18%). Conclusions This survey in the adult population has allowed a more complete description of the natural history of MALNS. Our findings will contribute to the development and improvement of standards of care for adults with MALNS to assure optimal health monitoring and treatment of evolutive complications. We propose additional recommendations to the previous dataset of clinical evaluations specifically applied to adults. The comparison of MALNS and SS adult presentation highlights significant differences in terms of prevalence and severity of ID, behavioral issues, and vision problems, confirming that a proper differential diagnosis between the two conditions is indispensable to guide physicians and mental health professionals to syndrome specific management.